Joint hypermobility syndrome subclassification in paediatrics: a factor analytic approach. Issue 1 (26th May 2014) - Pacey, Verity; Adams, Roger D; Tofts, Louise; Munns, Craig F; Nicholson, Leslie L
Abstract : Objective: To determine if exploratory factor analysis can identify subtypes comprising recognisable clinical patterns of the presenting signs and symptoms of children with joint hypermobility syndrome (JHS). Patients: Eighty-nine children with JHS aged 6–16 years. Methods: Twelve tests comprising anthropometric, musculoskeletal and functional assessments were conducted. Signs, symptoms and family history were recorded. Exploratory factor analysis was performed, factor scores generated, and correlations calculated to identify associations. Results: Sixty-six percent of the variance in the score set could be accounted for by five JHS subtypes (Eigenvalues >1). Factor 1, 'joint affected' JHS, had loadings on multiple joint pain, recurrent joint instability and postural orthostatic hypotension symptoms, and factor scores were associated with worse pain (r=0.48, p<0.01), fatigue (r=−0.54, p<0.01) and reduced health-related quality of life (HRQOL) (r=−0.5, p<0.01). Factor 2, 'athletic' JHS, loaded on muscle endurance, balance and motor skill proficiency, and scores were associated with less fatigue (r=0.3, p<0.01) and better HRQOL (r=0.44, p<0.01). Factor 3, 'systemic' JHS, loaded on skin involvement, incontinence symptoms, bowel involvement and recurrent joint instability, and was associated with reduced HRQOL (r=−0.24, p=0.03). Factor 4, 'soft tissue affected' JHS, loaded on recurrent soft tissue injuries and reduced muscle length, and was associated with greater fatigue (r=−0.43, p<0.01) and reduced HRQOL (r=−0.44, p<0.0001). Factor 5, 'high BMI' JHS, had high loadings on body mass index (BMI) for age, muscle endurance and no gastrointestinal involvement, and was associated with higher pain (r=0.33, p<0.01). Conclusions: The presenting signs and symptoms of children with JHS can be summarised in five clinically recognisable subtypes.